Kejayaan Kesultanan Buton Abad Ke-17 & 18 dalam Tinjauan Arkeologi Ekologi - Muhammad Al Mujabuddawat (Kapata Arkeologi, 2015)
Buton Sultanate is a prosperous maritime sultanate in its heyday. Buton Sultanate land is not very fertile and does not produce a lot of commodities, but it is quite well known because of its location in the commercial lines, so that it becomes a stopover place for passing ships. This paper provides an overview of ecological archaeology towards the triumph case of Buton Sultanate in the 17th-18th century. The research method used in this paper is literature study and review of a theory through an observation of cultural ecology and environmental determinism. The results show that the ecological aspects affect the heyday of the Buton Sultanate. Buton Sultanate does not produce a lot of major commodities, but it is successfully adapt to environmental conditions and maximize the benefits derived from the ecological aspects by applying it to the structure of Sultanate society, a commercial network, and material culture. The profits are also applied to maintain its legitimacy in the great power of hegemony in the region. Success in 'conquering' the environment makes the Buton Sultanate victorious, even the identity of 'kebutonan' still embedded in Buton society until this day.Kesultanan Buton merupakan kesultanan bercorak maritim yang cukup besar pada masa jayanya. Daratan Kesultanan Buton tidak begitu subur dan tidak banyak menghasilkan komoditi namun cukup terkenal karena lokasinya terletak di jalur niaga, sehingga menjadi lokasi singgah bagi kapal-kapal yang melintas. Penelitian ini berisi tinjauan arkeologi ekologi terhadap kasus kejayaan kesultanan Buton abad ke-17-18. Metode penelitian menggunakan studi pustaka dan tinjauan teori melalui tinjauan model cultural ecology dan environmental determinism. Hasil penelitian menunjukkan bahwa aspek-aspek ekologi berpengaruh terhadap kejayaan Kesultanan Buton. Kesultanan Buton tidak banyak menghasilkan komoditi utama, namun berhasil menyesuaikan diri dengan kondisi lingkungannya dan sukses memaksimalkan keuntungan-keuntungan yang diperoleh dari aspek ekologis. Dengan menerapkannya pada struktur masyarakat Kesultanan, jaringan perniagaan, budaya material, Kesultanan Buton mempertahankan legitimasi dalam hegemoni kekuatan besar di wilayahnya. Kesuksesan dalam ‘menaklukan’ lingkungan menjadikan Kesultanan Buton berjaya, bahkan hingga saat ini identitas ‘kebutonan’ masih melekat di dalam masyarakat Buton.